Global Infectious Diseases in February 2023: Monthly Analysis - Dongliang Liu; Guodan Li; Qun Su; Yi Luo; Taihan Li; Yufan Wu; Jiazhen Zou; Yinfu Sun; Qi Xiang; Shiping He; Wenjin Yu; Dayong Gu (Zoonoses)
Public health security in human societies is placed under enormous strain by infectious disease epidemics. According to the WHO, COVID-19 and Mpox remain on the list of PHEICs, whereas cholera, dengue, and other contagious diseases remain endemic in several countries and regions. Data on prevalent infectious diseases have been collected worldwide in recent weeks, and may provide new ideas for international collaboration in public health.